Enzymatic hydrolysis of oil palm empty fruit bunch using polyethylene glycol immobilized cellulase for fermentable sugar synthesis - Isah Nwaha Abdullahi, 1976- , author; Umi Aisah Asli, supervisor; Zainul Akmar Zakaria, supervisor; Fakulti Kejuruteraan Kimia (2014)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2014